2004
DOI: 10.1111/j.1574-0862.2004.tb00257.x
|View full text |Cite
|
Sign up to set email alerts
|

The economic determinants of cereal crop diversity on farms in the Ethiopian highlands

Abstract: In less favoured areas such as the highlands of Ethiopia, farmers manage risk through land allocation to crops and varieties since they cannot depend on market mechanisms to cope. They also grow traditional varieties that are genetically diverse and have potential social value. Supporting the maintenance of crop and variety diversity in such locations can address both the current needs of farmers and future needs of society, though it entails numerous policy challenges. We estimate a model of crop and variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 21 publications
13
55
0
1
Order By: Relevance
“…Similarly, households with larger land size are associated with greater crop diversity (P ≥ 0.001). These findings are also similar to those of Benin et al (2004) who concluded that larger farm sizes are associated with greater diversity within cereal crops. The coefficient for non-farm income is also significant (P ≥ 0.001) but negative, implying that a unit increase in non-farm income decreases the degree of multiple cropping patterns.…”
Section: Factors Driving Crop Diversificationsupporting
confidence: 81%
“…Similarly, households with larger land size are associated with greater crop diversity (P ≥ 0.001). These findings are also similar to those of Benin et al (2004) who concluded that larger farm sizes are associated with greater diversity within cereal crops. The coefficient for non-farm income is also significant (P ≥ 0.001) but negative, implying that a unit increase in non-farm income decreases the degree of multiple cropping patterns.…”
Section: Factors Driving Crop Diversificationsupporting
confidence: 81%
“…Lack of access to markets forces these farmers to adopt subsistence strategies which rely on sustained maintenance of internal resources by highly diversified systems. Similar results were found in other studies: in Mexico (Van Dusen 2000), in Ethiopia (Benin et al 2003) and at various locations in the Andes (Brush et al 1992).…”
Section: Agro-biodiversity and Soil Degradation Changes (2000-2005)supporting
confidence: 81%
“…(Di Falco et al 2007;Kebebew et al 2001), finger millet (Eleusine coracana) (Tsehaye et al 2006), and tef (Eragrostis tef) (Assefa et al 2001). A notable exception to these descriptive studies in Ethiopia is a study by Benin et al (2003), which revealed determinants of cereal crop diversity. They found higher diversity on farms far from the nearest towns or markets, with higher livestock assets and higher education of family members.…”
Section: Agro-biodiversity and Soil Degradation Changes (2000-2005)mentioning
confidence: 99%
“…Literature abounds with examination of factors influencing mainly adoption of modern technology in crop production at the farm level usually focusing on single crop only [24,25], although in reality farmers produce multiple crops [26][27][28]. In this study, we aim at identifying farmers' decision to diversify into multiple food crop production vis-à-vis profits generated therefrom.…”
Section: Introductionmentioning
confidence: 99%